BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI UNTUK KINERJA DOSEN PTS (Studi Kasus PTS di Samarinda) - SUYANTO SUYANTO; MARDIONO MARDIONO (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2019)
Lecturers have a very important role in determining the success and sustainability of the education sector so that lecturers are required to have high performance. The positive impact on the high performance of lecturers is not only for individuals but also on institutions, as the task of lecturers through educational institutions where work is obliged to produce quality students, and be able to compete in the global era. If the performance of lecturers is low the impact is the graduates produced are also questioned and doubted, by the job market. For this reason, the performance of lecturers is very important to always be improved, to ensure the future of the nation's young generation is able to compete in all respects. Lecturer performance is influenced by several factors developing lecturer performance, including organizational culture, and commitment to the organization. This research is explanatory or explanatory research. This type of observational research with design The number of samples as many as 88 respondents from 737 findings in this study is that organizational culture has a positive and significant effect on the performance of PTS lecturers in Samarinda, the better the organizational culture in each campus will tend to improve the performance of lecturers. Organizational commitment has a negative and not significant effect on the performance of PTS lecturers in Samarinda. Lecturers are not easy if they are demanded to have high commitment because most lecturers are more likely to interact on campus when there are teaching schedules.